Resection of pancreatic cancer in Europe and USA: an international large-scale study highlighting large variations - Huang, Lei; Jansen, Lina; Balavarca, Yesilda; Babaei, Masoud; Becker, Nikolaus; Hackert, Thilo; Büchler, Markus W.; Schrotz-King, Petra; Brenner, Hermann (Gut, 2019)
Objective: Resection can potentially cure resectable pancreatic cancer (PaC) and significantly prolong survival in some patients. This large-scale international study aimed to investigate variations in resection for PaC in Europe and USA and determinants for its utilisation. Design: Data from six European population-based cancer registries and the US Surveillance, Epidemiology, and End Results Program database during 2003-2016 were analysed. Age-standardised resection rates for overall and stage I-II PaCs were computed. Associations between resection and demographic and clinical parameters were assessed using multivariable logistic regression models. Results: A total of 153 698 records were analysed. In population-based registries in 2012-2014, resection rates ranged from 13.2% (Estonia) to 21.2% (Slovenia) overall and from 34.8% (Norway) to 68.7% (Denmark) for stage I-II tumours, with great international variations. During 2003-2014, resection rates only increased in USA, the Netherlands and Denmark. Resection was significantly less frequently performed with more advanced tumour stage (ORs for stage III and IV versus stage I-II tumours: 0.05-0.18 and 0.01-0.06 across countries) and increasing age (ORs for patients 70-79 and ≥80 versus those <60 years: 0.37-0.63 and 0.03-0.16 across countries). Patients with advanced-stage tumours (stage III-IV: 63.8%-81.2%) and at older ages (≥70 years: 52.6%-59.5%) receiving less frequently resection comprised the majority of diagnosed cases. Patient performance status, tumour location and size were also associated with resection application. Conclusion: Rates of PaC resection remain low in Europe and USA with great international variations. Further studies are warranted to explore reasons for these variations.
Published online first: 20 November 2017
Gesehen am 13.02.2019